Elvitegravir/Cobicistat/Emtricitabine/Tenofovir DF in HIV-Infected Patients With Mild-to-Moderate Renal Impairment. (1st March 2015) - Post, Frank A.; Winston, Jonathan; Andrade-Villanueva, Jaime F.; Fisher, Martin; Liu, YaPei; Beraud, Christophe; Abram, Michael E.; Graham, Hiba; Rhee, Martin S.; Cheng, Andrew K.; Szwarcberg, Javier
Abstract : Abstract: In HIV-1–infected treatment-naive patients with mild-to-moderate renal impairment [creatinine clearance (CrCl): 50–89 mL/min], elvitegravir/cobicistat/emtricitabine/tenofovir DF (STB, n = 33) achieved high rates of virologic success (78.8%; 95% confidence interval: 61.1% to 91.0%) and was well tolerated through week 48. Four patients discontinued study drug due to an adverse event and none due to proximal renal tubulopathy. As expected, decreases in CrCl were noted as early as week 2, after which they stabilized. The renal safety profile of STB in patients from this study is consistent with the long-term experience in a large number of patients with CrCl ≥70 mL/min.